Assessment of dermal exposure and skin condition of workers exposed to nickel at a South African base metal refinery - Du Plessis, Johannes L; Eloff, Frederik C; Badenhorst, Casper J; Olivier, Johretha; Laubscher, Petrus J; Van Aarde, Michiel N; Franken, Anja (The Annals of occupational hygiene, 2010)
The objectives of this study were to assess dermal exposure of cell workers to nickel at a South African base metal refinery and to characterize their skin condition by measuring the skin hydration and trans epidermal water loss (TEWL) indices. The skin hydration index of the index finger, palm, neck, and forehead was measured before, during and at the end of the shift. The TEWL index was measured before and at the end of the shift. Dermal exposure samples were collected with Ghostwipes from the index finger and palm of the dominant hand, before, during, and at the end of the shift. Neck and forehead samples were collected before and at the end of the shift. Wipe samples of various surfaces in the workplace were also collected. Wipes were analyzed for nickel according to NIOSH method 9102, using inductively coupled plasma-atomic emission spectrometry. Hydration indices measured on the hands decreased significantly during the shift, but recovered to normal levels by the end of the shift. TEWL indices for the index finger and palm of the hands are indicative of a low barrier function even before commencement of the shift, which further deteriorated significantly during the shift. During the shift, substantial nickel skin loading occurred on the index finger and palm of the hand. Levels on the neck and forehead were much lower. Various workplace surfaces, which workers come into contact with, were also contaminated with nickel. The skin condition and high levels of nickel on the skin were most probably caused by inadequate chemical protection provided by protective gloves. Although, the permeability of nickel through intact skin is considered to be low, a decreased barrier function of dehydrated or slightly damaged skin will increase its permeability for nickel. The ethnicity of these exposed workers may contribute significantly toward the low incidence of allergic contact dermatitis observed. Several measures to lower dermal exposure to nickel are also recommended.